Low‐frequency waves in the Martian magnetosphere and their response to upstream solar wind driving conditions. Issue 21 (5th November 2015) - Ruhunusiri, Suranga; Halekas, J. S.; Connerney, J. E. P.; Espley, J. R.; McFadden, J. P.; Larson, D. E.; Mitchell, D. L.; Mazelle, C.; Jakosky, B. M.
Abstract: We characterize low‐frequency plasma waves in the Martian magnetosphere and in the upstream region by using transport ratios. To compute the transport ratios, we use Mars Atmosphere and Volatile EvolutioN mission's (MAVEN) solar wind ion analyzer and suprathermal and thermal ion composition instrument measurements of the ion moments and the magnetometer measurements of the magnetic field. We find that the Alfvén waves are the most dominant wave mode in the upstream region and the magnetosheath. Fast waves are found frequently near the bow shock and the magnetic pileup boundary. Mirror and slow waves, on the other hand, occur much less frequently. We also find that the Alfvén and fast wave occurrences vary dominantly near the bow shock in response to the solar wind dynamic pressure. Key Points: Transport ratios are used for characterization of low‐frequency plasma waves at Mars Alfvén and fast waves have the highest occurrence ratios in the Martian magnetosphere Waves near the bow shock exhibit occurrence variability in response to solar wind dynamic pressure